The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bmjopen-2018-025818
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, double-blinded, placebo-controlled trial to investigate the role of laparoscopic transversus abdominis plane block in gastric bypass surgery: a study protocol

Abstract: IntroductionEvaluating the efficacy of a laparoscopically guided, surgical transversus abdominis plane (TAP) and rectus sheath (RS) block in reducing analgesic consumption while improving functional outcomes in patients undergoing laparoscopic bariatric surgery.Methods150 patients Living with obesity undergoing elective laparoscopic Roux-En-Y gastric bypass for obesity will be recruited to this double-blinded, placebo-controlled randomised controlled trial from a Bariatric Centre of Excellence over a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…TAP blocks have other advantages over fascial or plane blocks, as they can be safely performed under general anesthesia (66). Although our results suggest that TAP blocks should be considered for routine use, it is necessary and would be advantageous to look for larger RCTs to establish their evidence, such as the proposed study by Jarrar, et al (62).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…TAP blocks have other advantages over fascial or plane blocks, as they can be safely performed under general anesthesia (66). Although our results suggest that TAP blocks should be considered for routine use, it is necessary and would be advantageous to look for larger RCTs to establish their evidence, such as the proposed study by Jarrar, et al (62).…”
Section: Discussionmentioning
confidence: 79%
“…We also observed that time to ambulate was significantly lower in the TAP group. Decreased time to ambulate facilitates recovery, hence we note that the ERAS society makes strong recommendations for its use in minimally invasive colonic surgery, even with moderate quality of evidence (62). This must be contrasted with other opioid-sparing agents, such as gabapentinoids (63) or infusions of dexmedetomidine (64,65), which can cause sedation and increase time of discharge from recovery, affecting ERAS negatively.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions, including the 6-min walk test and peak expiratory flow rate, are intended to concurrently prepare patients, engage them in their own care, and improve their functional status before bariatric surgery. [ 3 4 ]…”
Section: Preoperative Preparationmentioning
confidence: 99%
“…Ongoing work at our center and elsewhere are looking at how better education can help set realistic expectations for the postoperative period with regards to reducing pain, analgesic requirements, and expected side effects. [ 3 4 5 ] For this, we have seen the evolution of patient education from hard copy booklets and web-based programs to app-based interactive modules providing patients in contemporary bariatric programs with the necessary tools to have the best possible experience and outcomes.…”
Section: Preoperative Preparationmentioning
confidence: 99%
See 1 more Smart Citation